NEUROENDOCRINE TUMOUR OF UNKNOWN PRIMARY ORIGIN: UNUSUAL CASE OF METASTATIC HEPATIC FOCI IN A FEMALE PATIENT - Khan, Anosh Aslam; Bin Waqar, Syed Hamza; Mohiuddin, Osama; Ehtesham, Moiz; Jalees, Sumeen (Journal of Ayub Medical College Abbottabad, 2020)
Under the banner of cancers of unknown primary origin (CUPs), neuroendocrine tumours account for less than five percent of the neoplasms. The clinical manifestations and management depend upon the tumour's grade and differentiation and its site of growth. At times, despite of aggressive search for primary origin, cancer remains hidden. Herein, we present a case of a middle-aged woman who presented to our tertiary set-up with complaints of abdominal pain and distension. After a series of radiologic and interventional investigations including positron emission tomography with liver biopsy and immunohistochemical analysis, a diagnosis of the well-differentiated neuroendocrine tumour was made, located in the right lobe of the liver. However, the primary origin could not be identified. The patient was managed with trans-arterial chemoembolization (TACE) followed by hepatic resection and was followed biennially afterwards. In our case, hepatic metastasis was treated with chemoembolization and staged-resection and provided a good prognosis to the patient. Our case is unique as only a few case reports have been published with following presentation and documentation of efficacious treatment is needed to contribute to the literature. Proper trials with exteriorization of bowel and radiological imaging is necessary to stage the primary tumour, even if end result is in vain. This will help to further improve the prognosis. Keywords: Neuroendocrine tumour; cancer of unknown aetiology; metastasis; TACE